DIMENSI KOMODIFIKASI MUSHAF ALQURAN: (Analisis Komodifikasi Mushaf Al-Qur’an Era Kontemporer) - Akhdiat, Akhdiat; Marisa, Siti Nurkhafifah (Prodi Ilmu Al-Qur'an dan Tafsir, 2023)
One of the ways to maintain the authenticity of the Quran now is by printing and publishing official mushaf, which is regulated through a decree of the Minister of Religious Affairs of the Republic of Indonesia. And the phenomenon of industrialization has spread to various aspects of life, even religion. The Quran is a religious symbol that has experienced the most industrialization process through the Quran printing process. Therefore, this article aims to analyze the extent of the commodification of the Quran in Indonesia so that the Mushaf becomes a commodity. Using a qualitative method and descriptive-analytical techniques with the lens of religious commodification, this paper finds that the market for Quran copies in the contemporary era is those who are technologically literate. Thus, Quran copies are printed on a large scale and marketed in offline and online stores with the aim of meeting people's needs for the Quran. Therefore, the commodification process is based on the people's need for the Quran which is increasing from time to time, and is supported by government policies related to the printing of the Quran copies. Even though the Quran copies are printed without using attachments and additional features but purely the text of the Quran, the copies will still become commodities. Due to the increasing demand of the community for the Mushaf and becoming a business field for Mushaf printing, it results in a process of production by producers and consumption by consumers, which then results in buying and selling transactions of Quran copies. And in the end there was a dimension of commodification in the manuscripts of the Koran.